PENELITIAN DOSEN DAN MAHASISWA TENTANG PERSEPSI MAHASISWA TERHADAP IMPLEMENTASI KODE ETIK DOSEN DALAM PENGAJARAN DAN KODE ETIK DOSEN TERHADAP MAHASISWA DI POLITEKNIK NEGERI SRIWIJAYA - Muhammad Riska Maulana; M. Nizar Al Rasyid; Mey Siska; Yolanda Yolanda; Putri Rahayu (Politeknik Negeri Sriwijaya, 2016)
This research was motivated by the question of the extent to which implementation of the Code of Conduct in Environmental State Polytechnic of Sriwijaya. As for the new study focused on the implementation of the Code Lecturer in the Field of Teaching and Implementation of the Code Lecturer Against Students in all majors at the Polytechnic of Sriwijaya. Respondents in the study drawn as many as 369 samples from the 4823 student population and sampling using nonprobability Sampling method with purposive sampling technique. The results showed that the overall implementation of the Code of Ethics Lecturer In teaching reached 77.348 or better value, while the implementation of the Code of Conduct Against Lecturer of students reaching 77.656 or better value.